FORMULASI DAN SIFAT ORGANOLEPTIK NUGGET BERBASIS TEMPE DAN SERBUK DAUN KELOR SEBAGAI MAKANAN SELINGAN TINGGI KALSIUM UNTUK LACTO-OVO VEGETARIAN - Salsabila, Rifa; Rosmana, Dadang; Mahmudah, Umi; Priawantiputri, Witri; Fikri, Elanda (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2022)
A problem for vegetarians is the risk of calcium deficiency. Nuggets made from tempeh and moringa leaf powder can be used as an alternative for additional foods that contain calcium so that it is expected to reduce the risk of osteoporosis. This study aims to obtain a formula and determine the effect of the balance of nugget and Moringa leaf powder on the organoleptic properties of nuggets, as well as to determine the calcium levels in each balance. The research design is experimental, the research method used is hedonic test for testing organoleptic properties and spectrophotometry for testing calcium levels. The research was carried out in January 2021 by sending products to the homes of 30 panelists by implementing health protocols related to the COVID-19 pandemic. This nugget formula consists of a balance, with a ratio of tempeh and Moringa leaf powder (%) F1 (97% : 3%) F2 (94% : 6%), and F3 (91% : 9%). The results of statistical tests showed that there was no difference in the aspects of color, taste, texture and overall. As for the aroma, there was a significant difference between the F2 and F3 nuggets. Calcium levels of F1, F2, and F3 produced are 16.4; 16.6 and 16;8 mg/100gr. It is necessary to modify and further research on the manufacture of nuggets with other vegetable protein sources so that the product has a high calcium content so that it can increase calcium in the body, especially for lacto-ovo vegetarians.